1997
DOI: 10.1007/pl00005012
|View full text |Cite
|
Sign up to set email alerts
|

Daily rhythms of heart rate, temperature and locomotor activity are modified by anaesthetics in rats: a telemetric study

Abstract: The aim of this study was to evaluate the effect of anaesthesia (ether or ketamine) on daily rhythms of temperature (T), heart rate (H) and locomotor activity (A) in unrestrained rats by using implanted radio-telemetry transmitters. T, H and A were measured every 10 min, in Wistar male rats, and analysed using Cosinor. The mean +/- SEM days needed, after surgical implantation, to detect a daily rhythm in H, T and A were also assessed. Six rats were anaesthetized for about 50 min either by ketamine or ether in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 13 publications
1
27
1
2
Order By: Relevance
“…This type of anaesthesia modifies acrophase, mesor, and amplitude of the daily rhythms, but without loss of the daily rhythmicity [27,28]. The preservation of LD dependence in the HR after the surgical interventions in our experimental model does not affirm the assumption that surgery can have a more marked effect on LD dependence than the simple effect of the anaesthetic agent [28].…”
Section: The Effects Of Ld Cycle On the Cardiovascular Reactivity In contrasting
confidence: 54%
“…This type of anaesthesia modifies acrophase, mesor, and amplitude of the daily rhythms, but without loss of the daily rhythmicity [27,28]. The preservation of LD dependence in the HR after the surgical interventions in our experimental model does not affirm the assumption that surgery can have a more marked effect on LD dependence than the simple effect of the anaesthetic agent [28].…”
Section: The Effects Of Ld Cycle On the Cardiovascular Reactivity In contrasting
confidence: 54%
“…Some studies suggest that general anesthetics disturb the circadian rhythms in the days following. The induction of ether or ketamine anesthesia during the resting phase (light period) of rodents has been shown to alter the daily rhythms of heart rate, body temperature and locomotor activity in the days following (Prudian et al, 1997). In humans, anesthesia and surgery with operative stress delay the onset of nocturnal melatonin secretion during the first postsurgical evening, suggesting a phase shift in the circadian secretion of melatonin Karkela et al, 2002;Reber et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Light-dark dependence of electrocardiographic changes during asphyxia and reoxygenation in a rat model not in the PQ interval. This means that the significant LD differences in ECG parameters refer to fact that ketamine/xylazine anaesthesia does not disturb lightdark dependence, but it can modify acrophase, mesor, and amplitude of the circadian rhythms without loss of daily rhythmicity [34,35]. We found that circadian rhythm was present in the rats' heart rate before implantation of the transmitters (for the recording of heart rate) and that non-detection of a daily rhythm after implantation of the transmitters under general anaesthesia was essentially due to surgical aggression; the general anaesthetic agent was responsible only for perturbations of the characteristics of this rhythm.…”
Section: Discussionmentioning
confidence: 99%